Stand biomass of Pinus sylvestris var. mongolica plantations benefits from high density monocultures in the boreal zone - Bingming Chen; Shensi Liu; Jinghua Yu; Yanqing Huang; Shuai Yu; Huanchu Liu; Tianyu Zhang; Xiangdong Liu; Guangze Jin; Wei Chen; Xingyuan He (Forest Ecosystems)
Pinus sylvestris var. mongolica (P. sylvestris) plantations are extensively established in the boreal zone. Increasing stand biomass of these plantations can effectively enhance carbon stock, which is crucial for mitigating climate change. However, the current understanding of optimizing plantation strategies to maximize stand biomass is primarily derived from experiments in tropical and subtropical zones, which is difficult to extend to the boreal due to substantial climatic differences. Based on a comprehensive dataset from 1,076 sample plots of P. sylvestris plantations in the boreal zone of China, we evaluated the effects of tree species richness and stand density on tree height, diameter at breast height (DBH), and stand biomass to investigate the optimal plantation strategy. Furthermore, we examined how these effects changed with stand age and investigated their relative importance. We found that monocultures at a high stand density of 2,000–2,500 ​ha−1 were the optimal plantation strategy to maximize stand biomass (107.5 ​Mg·ha−1), and this held true at almost all stand ages. Unfortunately, this strategy resulted in low species richness and small individual trees (10.6 ​m height and 9.8 ​cm DBH), thus presenting a trade-off. In addition, as stand age increased, the effect of tree species richness on stand biomass shifted from positive to negative, but the effect of stand density was always positive. Overall, stand age had the greatest effect on stand biomass, followed by stand density and then tree species richness. Our findings reveal a distinct plantation strategy for optimizing stand biomass of P. sylvestris plantations in the boreal zone. More importantly, this study highlights that (1) maximizing stand biomass in the boreal zone may compromise tree species richness; (2) net effects of tree species richness on stand biomass are not always positive, as negative selection effects offset positive complementary effects.